Repeated sprint ability demands in U16 to U19 highly trained handball players concerning playing position - Starczewski, M.; Borkowski, L.; Zmijewski, P. (International Journal of Environmental Research and Public Health, 2020)
The aim of the study was to determine anaerobic capacity and characterize changes in repeated sprint ability (RSA) within youth elite handball players. For this study, 142 male athletes (17.1 ± 0.9 years) were recruited from a handball sports high school and performed the RSA test on a cycle ergometer, including five 6 s all-out efforts separated by 24 s passive breaks. Maximal (Pmax) and mean (Pmean) power, highest (Wmax), and total work (Wtot) as well as power (Pdec) and work (Wdec) decrement were measured. Significant differences in RSA were noted in relation to age (greater values of Pmax, Pmean, Wtot, Wdec, and Pdec in U19 than U17 as well as greater values of Pmax, Wtot, Wmax, Wdec, and Pdec in U19 than U16 (p < 0.05)) and playing position (wing players had greater Wtot than pivot, 269 vs. 243 (J/kg) (p < 0.05), and wing players differed significantly in absolute and relative power from athletes of other positions). RSA depends on playing position and age in groups of youth handball players and the RSA test can be helpful in the selection of athletes for a playing position. The article introduces normative values for elite youth handball players, empowering coaches in the evaluation of anaerobic abilities and selection.